(untitled) (Research, Society and Development, 2023)
The new coronavirus pandemic imposed another condition of life in the personal and professional spheres, forcing us to reorganize our individual and collective activities. From the study of the impositions and limitations promoted by this new social context, this text, ranked among the top five nationally by Edict Capes/2022, discusses the social and psychological impacts suffered by an ICU nurse and his family. To do so, we analyzed scientific works on the theme, reports, impressions, and experiences of professionals and other people involved in these new conditions arising from the pandemic, as well as their impacts. Thus, this study aimed to offer subsidies to better understand patients’ general health conditions and the procedures to be adopted, emphasizing teamwork. We present the data through three reports of experiences, showing the difficulties amidst many restrictions, condition directly affected by the psycho-social impacts of uncommon work conditions. The same data also point out ways to overcome the barriers, such as the use of information and communications technology (ICTs) and possibilities to resignify social and work relations.